Physician-patient Interactions in African American Patients with Systemic Lupus Erythematosus: Demographic Characteristics and Relationship with Disease Activity and Depression - Drenkard, Cristina (Semin Arthritis Rheum, 2018)
OBJECTIVE: African American patients with systemic lupus erythematosus (SLE) are at high risk for poor outcomes. Both patient characteristics and the severity of the disease may influence physician-patient interactions, which in turn can impact disease outcomes. We aimed to examine whether patient perceptions of interpersonal processes of care (i.e. physician-patient interactions) varied by demographic characteristics, disease activity, and/or depression in African American patients with SLE. METHODS: The Georgians Organized Against Lupus (GOAL) is a cohort drawn from a population-based registry of people with SLE. We conducted a cross-sectional analysis of patient-reported data collected in 2016–17 among 698 African American participants (out of 863 GOAL participants). We assessed physician-patient interactions (communication, patient-centered decision making, and physician interpersonal style) through the Interpersonal Processes of Care survey (IPC-29), disease activity through the Systemic Lupus Activity Questionnaire, and depression through the Patient Health Questionnaire-9. Mean scores of the IPC-29 scales were compared by gender, age and educational attainment with Wilcoxon rank-sum 2-sample test or Kruskal Wallis test. We conducted linear trend test to examine demographic-adjusted scores of IPC across severity of disease activity and depression, and multivariate logistic regression analyses to examine the association of disease activity and depression with suboptimal IPC scores. RESULTS: Overall, the lowest mean scores were observed for the patient-centered decision making domain, and specifically about how often doctors assessed patients’ problems to follow recommendations and treatment among females compared with males (mean scores 3.13 ± 1.42 and 3.64 ± 1.38, respectively; p=0.015). Mean scores for the assumed socioeconomic level subdomain (how often doctors make assumptions about a patient’s socioeconomic level) were worse in individuals aged 18–34 (mean score 1.59 ± 0.94), compared to those aged 35–55 (mean score 1.47 ± 0.94; p=0.033). Patients with some college or higher educational attainment reported poorer mean scores for most communication and interpersonal style scales than those who reported high-school or less. We found significant linear trends of poorer scores for all communication scales across more severe disease activity and depression symptoms, and poorer scores for all interpersonal style scales across more severe disease activity. Multivariate models revealed that while depression was associated with suboptimal quality of both communication (OR 1.20; 95% CI 1.04–1.39) and interpersonal style (OR 1.12; 95% CI 1.01–1.25), disease activity only increased the odds of suboptimal interpersonal style (OR 1.13; 95% CI 1.03–1.25). CONCLUSION: In the African American population with SLE, suboptimal interactions with providers may be explained in part by the mental and physical symptoms of the patient, regardless of age, gender and education. In addition to standard of care treatment, SLE patients with more severe disease activity and depression might need provider-based interventions focused on communication and interpersonal style.